Model of Democratic/Authoritative Parking of Lecturers in Developing Student Academic-Leadership Potentials - Suyudi, Muhamad; Mahmudah, Ummi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This research aims to explain the democratic parenting model of INSURI Ponorogo lecturers in developing the academic-leadership potential of female students who become foster children. This research is qualitative with a case study approach. In this case, the researcher describes the parenting style of INSURI Ponorogo lecturers to female students appointed as foster children. Can this parenting style develop students' academic leadership potential or not? As a case study research, the population and research sample totaled five lecturers and twenty foster students affiliated with INSURI Ponorogo. The research data is in the form of parenting activities of lecturers toward female students. Sources of data were obtained from lecturers, students, and documentation. Observation, interviews, and documentation carried out research data collection techniques. In comparison, data analysis is done by data reduction, presentation, conclusion, and verification. The study results show that the activities of democratic/authoritative parenting styles carried out by lecturers for female students are different. Parenting style leads to developing academic potential, responsibility, leadership, educational, social, and economical, such as guiding, involving community organizations and student organizations, entrepreneurship, and deepening religious knowledge. The democratic parenting model of INSURI Ponorogo lecturers is bearing fruit. It has been proven that some female students who experience this parenting style have achieved good academic achievements and leadership skills.